2019
DOI: 10.1002/adom.201901388
|View full text |Cite
|
Sign up to set email alerts
|

Seed‐Initiated Synthesis and Tunable Doping Graphene for High‐Performance Photodetectors

Abstract: Due to the promising utilizations in nanoelectronics, doping‐tunable graphene is paid extensive attentions. Nevertheless, a harmless approach to dope/co‐dope graphene in a controllable and easy way with low cost is still unattainable. Herein, through seeding of 0D N & S dual‐doped graphene quantum dots (N & S dual‐doped GQDs) on a catalytic substrate and then dynamic chemical vapor deposition (CVD), a monolayered dual‐doped graphene film is demonstrated. The concentrations of dopants in graphene are strictly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The typical characteristic bands of 3D‐Gr that are the D ‐band (1350 cm −1 ), G ‐band (1580 cm −1 ), and 2 D ‐band (2700 cm −1 ) appear. [ 14,15 ] The distinct D ‐band existing in all samples can be attributed to the abundantly exposed edges of nanosized 3D‐Gr. In addition, all samples exhibit a shoulder peak around at 1620 cm −1 , which is named as D ′‐band.…”
Section: Resultsmentioning
confidence: 97%
“…The typical characteristic bands of 3D‐Gr that are the D ‐band (1350 cm −1 ), G ‐band (1580 cm −1 ), and 2 D ‐band (2700 cm −1 ) appear. [ 14,15 ] The distinct D ‐band existing in all samples can be attributed to the abundantly exposed edges of nanosized 3D‐Gr. In addition, all samples exhibit a shoulder peak around at 1620 cm −1 , which is named as D ′‐band.…”
Section: Resultsmentioning
confidence: 97%
“…Despite the fact that sulfur does not fit in the graphene plane and bulges out of the sheet, the most studied codoped graphene system is sulfur and nitrogen codoped graphene. There are so many articles published about this system …”
Section: Codoped or Dual-doped Graphenementioning
confidence: 99%
“…Efficient photocatalytic H 2 O 2 production was achieved since the codoped graphene induced a better light absorption and promoted a more significant charge migration . Sulfur and nitrogen codoped graphene nanomaterials have broad visible absorption , and superb luminescence properties. They can be used in bioimaging. , Also, they were reported to have a fluorescence quantum yield 9.3 times higher than that of undoped graphene. Thus, they are promising materials for developing light-emitting devices …”
Section: Codoped or Dual-doped Graphenementioning
confidence: 99%
“…And it has been shown that doping Si on carbon‐based materials will change the catalyst surface electron arrangement or surface acidity or alkalinity, thus affecting the catalytic performance [12, 39, 40]. In this work, catalyst models of Fe‐loaded on pure graphene quantum dots [41, 42] (Fe‐C 4 ) and Fe‐loaded on N‐doped modified graphene quantum dots (Fe‐N 4 ) and Fe‐loaded on Si‐doped modified graphene quantum dots (Fe‐Si 4 ) were constructed. The adsorption properties of CO 2 on Fe‐C 4 and Fe‐N 4 and Fe‐Si 4 and the reaction mechanisms of CO 2 hydrogenation to formic acid over these three catalysts were investigated using DFT calculations.…”
Section: Introductionmentioning
confidence: 99%